Walt Disney's Cinderella Atelier Philippie Harchy ; story adaptation by Robyn Bryant. - Atelier Philippe Harchy; Bryant, Robyn (The Walt Disney Princess treasure chest, 1993)
With the help of her fairy godmother, a kitchen maid mistreated by her stepmother and stepsisters attends the palace ball where she meets the prince of her dreams.